Microbiological, morpho-textural, and volatile characterization of Portuguese Queijo de Nisa PDO cheese. (December 2022) - Cardinali, Federica; Foligni, Roberta; Ferrocino, Ilario; Harasym, Joanna; Orkusz, Agnieszka; Milanović, Vesna; Franciosa, Irene; Garofalo, Cristiana; Mannozzi, Cinzia; Mozzon, Massimo; Cocolin, Luca; Aquilanti, Lucia; et al.
Graphical abstract: Highlights: Microbiota and volatile compounds in Queijo de Nisa PDO cheese were studied. Lc. lactis and Ln. mesenteroides were detected at high relative frequency. L. plantarum, L. piscium, and L. zeae were also detected. Carboxylic acids, carbonyl compounds, alcohols, and esters were the main VOCs. Abstract: Queijo de Nisa PDO (Protected Designation of Origin) is a semi-hard cheese obtained from raw ewe's milk clotted with cardoon ( Cynara cardunculus, L.) rennet. The aim of the present study was to characterize the bacterial communities naturally occurring in Queijo de Nisa PDO cheese samples through viable counting and metataxonomic analysis. Moreover, physico-chemical and morpho-textural analyses were also performed, together with the analysis of volatile organic compounds (VOCs) through solid-phase microextraction (SPME) coupled with gas chromatography-mass spectrometry (GC–MS). In the analyzed samples, pH values were comprised between 4.84 and 5.74. As for lactic acid, the concentration varied between 0.83 and 2.10 g 100 g -1 . Water activity varied between 0.942 and 0.960. Lightness of the samples ranged from 107.82 to 119.16, whereas hardness ranged between 34.45 N and 126.05 N. As for microbiological analyses, lactococci and lactobacilli counts were up to 9.01 Log CFU g -1 . Coagulase-negative cocci and enterococci counts were up to 7 Log CFU g -1 . Metataxonomic analysis revealed that Lactococcus lactis and Leuconostoc mesenteroides occurred at high frequency in all the analyzed samples. Moreover, Lactiplantibacillus plantarum, Lactococcus piscium, and Lacticaseibacillus zeae were also detected. The most represented VOCs were carboxylic acids, carbonyl compounds, alcohols, and esters. In the analyzed cheese samples, significant relationships between bacteria and VOCs were also evidenced. Of note, research on the microbiological and chemical features, as well as on morpho-textural characteristics, of Queijo de Nisa  PDO  cheese can increase the knowledge on the interactions between raw materials, environment, and autochthonous microorganisms, thus enabling protection of biodiversity and tradition.